Effects of Chemical and Auditory Cues of Hoopoes (Upupa epops) in Repellence and Attraction of Blood-Feeding Flies - Tomás, Gustavo; Zamora-Muñoz, Carmen; Martín-Vivaldi, Manuel; Barón, M. Dolores; Ruiz-Castellano, Cristina; Soler, Juan J. (Frontiers in Ecology and Evolution, 2020)
Research on the mechanisms involved in host location by parasites is of paramount importance and may aid in developing protective measures against them. This topic attains far-reaching repercussions for human and animal welfare regarding parasites transmitting vector-borne pathogens, such as blood-feeding flies. Very few studies have evaluated the effect of bird-derived cues on attraction of vectors in field conditions. We here explored the attraction of different groups of blood-feeding flies (mosquitoes, blackflies and biting midges) to auditory cues produced by begging hoopoe (Upupa epops) nestlings, and to three chemical cues derived from hoopoe nestlings or nests (uropygial secretion, symbiotic bacteria isolated from the secretion, and nest material) in the field. We deployed insect traps baited with the different stimuli at the beginning and at the end of the hoopoe breeding-season in four different habitats. Abundance of blood-feeding flies varied depending on habitat and sampling period. Begging auditory cues of nestling hoopoes did not affect abundance of flies. However, chemical stimuli affected abundance of mosquitoes, which were less abundant in traps baited with bacteria or with nest material than in control traps. Abundance of biting midges in traps also depended on the chemical stimulus but in interaction with sampling period or habitat. Fewer biting midges were collected in traps baited with bacteria and with secretion in the habitats where abundance of biting midges is higher. Our results suggest that uropygial secretion of hoopoes, and symbiotic bacteria living in this secretion, may repel blood-feeding flies from their nests.